ANALISIS FAKTOR FAKTOR YANG MEMPENGARUHI PRODUKTIVITAS REHABILITASI HUTAN DAN LAHAN SERTA MANFAATNYA TERHADAP MASYARAKAT DI KABUPATEN YAHUKIMO - Wakarmamu, Thobby; Bura, Semuel Tande; Lamba, Arung (JURNAL EKOLOGI BIROKRASI, 2015)
The current research aimed to study, analyze and find out (1) the sffect of profile, institution, fund, economy, andpolicy on forest and land rehabilitation productivity; (2) the effect of forest and land productivity and use on community income, work force absorption, community forest value added; (3) community perception on use of forest and land rehabilitation in Yahukimo Regency. The population of this research was all the people who were residents of the regency, 680 community groups who had received funds for rehabilitation of their critical lands, and with the 5% (0.005) probability of significance, the minimal sample taken was 250 respondents. The data was analyzed to answer the problems and to prove the hypotheses by using descriptive analysis and SEM (Structural Equation Mode). The result os the study showed that: (1) The five variables: profile, institution, funds, economy, and policy which were tested to find out their effect on the forest and land rehabilitation productivity in Yahukimo Regency had positive and significant effect on forest and land productivity in Yahukimo Regency. When it was ranked according to their effect institution, policy, profile gave considerable effect while funding variable gave little effect; (2) the three indicators of usage tested (increase, income, work force absorption and value added increase) that were tested for their use concerning forest and land rehabilitation productivity gave positive and significant effect; (3) the community showed positive perception on the use of forest and land rehabilitation in Yahukimo Regency as been by 3 (Three) indicators of use. Keywords : Forest and Land Rehabilitation